CANCER RISK ASSESSMENT INSTRUMENTS IN WOMEN: LITERATURE REVIEW - Devita Madiuw; Yanti Hermayanti; Tetti Solehati (Journal of Maternity Care and Reproductive Health, 2020)
Early detection of cancer or cancer screening is important. The right measurement tool is needed to conduct early detection of cancer. The instrument of assessment would help health workers in  the early detection of cancer in women. This literature review aimed to identify instruments for detecting the risk of cancer in women. The research method was a literature review, the articles were searched from four databases including CINAHL, Science Direct, Pubmed and Proquest. After the critical appraisal, there were 5 articles that fit the inclusion criteria, including the publication year from 2014 to 2019. The results found four instruments such as Breast cancer risk assessment (BCRA); Six Point Scale and Referral Screening Tool (RST); Perceived risk scale; Online self-test questionnaires. Not much research has been done using instruments to assess the risk of cancer in women. Limited instruments were found in this study even though the incidence of cervical cancer is also high. More research is needed to develop instruments for assessing cancer risk in women, especially cervical cancer. Key words: Early detection, risk assessment instrument, women’s cancer.